Development of indicators to assure quality of disability evaluation based on the International Classification of Functioning, Disability, and Health in Taiwan: a Delphi consensus. Issue 7 (26th March 2020) - Chang, Kwang-Hwa; Chi, Wen-Chou; Liao, Hua-Fang; Chen, Shih-Ching; Chiou, Hung-Yi; Escorpizo, Reuben; Liou, Tsan-Hon
Abstract: Purpose: To develop a set of quality indicators (QIs) for managing the International Classification of Functioning, Disability, and Health-based disability evaluation system in Taiwan. Method: Using a three-round Delphi exercise, 20 representatives from the social welfare associations for people with disability completed the consensus process. Questionnaire 1 comprised 52 potentially important factors relevant to good services for persons with disabilities in the system. An additional nine items were added to questionnaires 2 and 3. The responders rated the importance of each item using a 5-point Likert scale. The set of QIs for managing the system comprised items that obtained high consensus and a mean score ≥4.5 found in round 3. Results: Those QIs included a composite of measures about a comfortable and barrier-free assessment room, on-site assistance (being important for client access and safety), client's privacy, rights protection, and satisfaction, convenient service, attitude of staff (towards client centeredness), accuracy of report (system effectiveness), and competent staff (system efficiency). Spearman's rho (mean ± standard deviation) of round 3 was 0.79 ± 0.09, and Cronbach's α = 0.90. Conclusions: This set of QIs is suitable for managing the system serving people with disabilities. It is feasible in practice and scientifically acceptable, but further validation is needed. Implications for rehabilitation: With this study, we were able to develop a set of quality indicators for managing the International Classification of Functioning, Disability and Health-based disability evaluation system. The set of quality indicators included a composite of measures about a comfortable and barrier-free assessment room and on-site assistance; client's privacy, rights protection, and satisfaction, convenient service, attitude of staff; accuracy of report, and competent staff. These quality indicators foster client-centeredness, access, safety, system effectiveness and efficiency, feasibility, and science; and are relevant to managing a system that is intended to serve people with disabilities.